RADIO LABELING OF BANANA GRAPHS - Sarbaini Sarbaini; Nazaruddin Nazaruddin; Muhammad Rizki; Muhammad Isnaini Hadiyul Umam; Muhammad Luthfi Hamzah; Tegar Arifin Prasetyo (Barekeng)
Let G=(V, E) be a graph. An L(3,2,1) labeling of G is a function  such that for every , , and  if . Let , a  labeling is a labeling  where all labels are not greater than . An ) number of , denoted by , is the smallest non-negative integer  such that  has a  labeling. In this paper, we determine   of banana graphs.